Ischemic Colitis Arising in Watershed Areas of the Colonic Blood Supply: A Report of Two Cases - Yamazaki, Toshiyuki; Shirai, Yoshio; Tada, Tetsuya; Sasaki, Masataka; Sakai, Yasuo; Hatakeyama, Katsuyoshi (Surgery today (Tokyo, Japan), 1997)
There are several weak points in the colonic blood supply, known as watershed areas, which result from incomplete anastomoses of the marginal arteries. These watershed areas are more vulnerable to ischemic injury than other parts of the colon. We report herein the cases of two patients who developed ischemic colitis well localized in the cecum, and in the rectosigmoid region at Sudeck's point, respectively. This report and our review of the literature suggest that watershed areas, including the splenic flexure, or Griffith's point, Sudeck's point, and the ileocecal region, are high-risk regions for the development of ischemic colitis.